Johannes V. Jensen og Valdemar Vedel – nogle breve - Jørgensen, Aage (Danske Studier, 2024)
This article presents the scanty correspondence between the author Johannes V. Jensen and the critic Valdemar Vedel. As publisher of the periodical Tilskueren (The Spectator) during the ‘cultural battle’ that took place around 1900, Vedel adopted what he himself considered a ‘radical’ viewpoint regarding Brandesianism as represented by the newspaper Politiken whose editor-in-chief was Edvard Brandes. In 1898, Jensen reported on the Spanish-American War in Politiken, but sought and obtained advice from Vedel in connection with the publication of the articles in Den gotiske Renaissance (The Gothic Renaissance, 1901), just as Vedel in 1903 asked him to contribute to a series of articles, »How I became a writer”. When, in 1905, Brandes was replaced by Henrik Cavling, Jensen returned to Politiken where he published in 1907 an infamous attack on the homosexuals of intellectual life. Vedel’s opposition was subtle and he managed to get himself characterised by Jensen as a »Fruentimmersjæl«. That did not prevent him from praising Jensen’s artistry in several reviews.